Evaluating the outcomes of a podiatry‐led assessment service in a public hospital orthopaedic unit - Daniel R Bonanno; Virginia G Medica; Daphne S Tan; Anita A Spring; Adam R Bird; Jana Gazarek (Journal of Foot and Ankle Research, 2014)
Abstract Background In Australia, the demand for foot and ankle orthopaedic services in public health settings currently outweighs capacity. Introducing experienced allied health professionals into orthopaedic units to initiate the triage, assessment and management of patients has been proposed to help meet demand. The aim of this study was to evaluate the effect of introducing a podiatry‐led assessment service in a public hospital orthopaedic unit. The outcomes of interest were determining: the proportion of patients discharged without requiring an orthopaedic appointment, agreement in diagnosis between the patient referral and the assessing podiatrist, the proportion of foot and ankle conditions presenting to the service, and the proportion of each condition to require an orthopaedic appointment. Methods This study audited the first 100 patients to receive an appointment at a new podiatry‐led assessment service. The podiatrist triaged ‘Category 3’ referrals consisting of musculoskeletal foot and ankle conditions and appointments were provided for those considered likely to benefit from non‐surgical management. Following assessment, patients were referred to an appropriate healthcare professional or were discharged. At the initial appointment or following a period of care, patients were discharged if non‐surgical management was successful, surgery was not indicated, patients did not want surgery, and if patient's failed to attend their appointments. All other patients were referred for an orthopaedic consultation as indicated. Results Ninety‐five of the 100 patients (69 females and 31 males; mean age 51.9, SD 16.4 years) attended their appointment at the podiatry‐led assessment service. The 95 referrals contained a total of 107 diagnoses, of which the podiatrist agreed with the diagnosis stated on the referral in 56 cases (Kappa =0.49, SE = 0.05). Overall, 34 of the 100 patients were referred to an orthopaedic surgeon and the remaining 66 patients were discharged from the orthopaedic waiting list without requiring an orthopaedic consultation. Conclusions Two‐thirds of patients who had an appointment at the podiatry‐led assessment service were discharged without requiring a surgical consultation. The introduction of a podiatry‐led service assists with timely provision of patient care and ensures those with the greatest need for orthopaedic surgery have improved access to specialist care.